Angiotensin Receptor Neprilysin Inhibitor LCZ696 Attenuates Cardiac Remodeling and Dysfunction After Myocardial Infarction by Reducing Cardiac Fibrosis and Hypertrophy. (January 2015) - von Lueder, Thomas G.; Wang, Bing H.; Kompa, Andrew R.; Huang, Li; Webb, Randy; Jordaan, Pierre; Atar, Dan; Krum, Henry
<x xml:space="preserve">Abstract</x> Background— Angiotensin receptor neprilysin inhibitors (ARNi), beyond blocking angiotensin II signaling, augment natriuretic peptides by inhibiting their breakdown by neprilysin. The myocardial effects of ARNi have been little studied until recently. We hypothesized that LCZ696 attenuates left ventricular (LV) remodeling after experimental myocardial infarction (MI), and that this may be contributed to by inhibition of hypertrophy and fibrosis in cardiac cells. Methods and Results— One week after MI, adult male Sprague–Dawley rats were randomized to treatment for 4 weeks with LCZ696 (68 mg/kg body weight perorally; MI-ARNi, n=11) or vehicle (MI-vehicle, n=6). Five weeks after MI, MI-ARNi versus MI-vehicle demonstrated lower LV end-diastolic diameter (by echocardiography; 9.7±0.2 versus 10.5±0.3 mm), higher LV ejection fraction (60±2 versus 47±5%), diastolic wall strain (0.23±0.02 versus 0.13±0.02), and circular strain (−9.8±0.5 versus −7.3±0.5%; all P<0.05). LV pressure–volume loops confirmed improved LV function. Despite similar infarct size, MI-ARNi versus MI-vehicle had lower cardiac weights (P<0.01) and markedly reduced fibrosis in peri-infarct and remote myocardium. Angiotensin II–stimulated incorporation of 3[H]leucine in cardiac myocytes and 3[H]proline in cardiac fibroblast was used to evaluate hypertrophy and fibrosis, respectively. The neprilysin inhibitor component of LCZ696, LBQ657, inhibited hypertrophy but not fibrosis. The angiotensin receptor blocker component of LCZ696, valsartan inhibited both hypertrophy and fibrosis. Dual valsartan+LBQ augmented the inhibitory effects of valsartan and the highest doses completely abrogated angiotensin II–mediated effects. Conclusions— LCZ696 attenuated cardiac remodeling and dysfunction after MI. This may be contributed to by superior inhibition of LCZ696 on cardiac fibrosis and cardiac hypertrophy than either stand-alone neprilysin inhibitor or angiotensin receptor blocker.